Isolated lesser tuberosity fracture of the humerus literature review and case report - Ho, Man Truong Phu; Nguyen, Thanh Long; Nguyen, Dang Huy Nhat (Tạp chí Y Dược Huế, 2026)
Background: Isolated fractures of the lesser tuberosity of the humerus are exceptionally rare and often challenging to diagnose due to non-specific symptoms and their infrequent occurrence. The accurate diagnosis and timely treatment of such fractures are critical to prevent complications such as chronic shoulder pain and functional impairment. Objective: This study aims to review the clinical presentation, diagnostic challenges, and treatment outcomes associated with isolated lesser tuberosity fractures of the humerus. Additionally, we present two case reports that highlight the surgical management of these injuries and their outcomes. Methods: Both male patients, aged 31 and 35 sustained their injuries from falls and presented with acute shoulder pain and limited motion. Initial X-rays were inconclusive, leading to further imaging with CT scans, which confirmed the diagnosis. Both patients underwent open reduction and internal fixation (ORIF). Postoperative follow-up included serial radiographs and clinical assessment of shoulder motion. Results: ORIF restored the lesser tuberosity to its anatomical position in both cases. Follow-up radiographs demonstrated maintained reduction and progressive union, while clinical examination showed marked improvement in pain and shoulder function. At 3 months, case 1 had mild residual limitation of abduction and extension, whereas case 2 recovered near-full shoulder motion after rehabilitation. Conclusion: Isolated lesser tuberosity fractures, though rare, require careful clinical evaluation and imaging for accurate diagnosis. Early and accurate diagnosis of isolated lesser tuberosity fractures is crucial to prevent long-term complications. Surgical management, particularly ORIF, appears to be a reliable approach in treating these fractures, resulting in favorable outcomes. Further research is needed to establish standardized treatment protocols for these uncommon injuries